Identification of Historical Buildings in Menggala as a Learning Resource for Social Studies - Bibit Suranti; Karsiwan, Karsiwan (JURNAL PENDIDIKAN IPS, 2025)
Tulang Bawang Regency possesses numerous historical buildings that hold significant cultural and educational value. However, this potential has not been optimally utilized as a learning resource for Social Studies (IPS), resulting in students lacking contextual learning experiences based on local history. This study aims to identify historical buildings in Tulang Bawang Regency and explore their potential as learning resources for Social Studies. Using a descriptive qualitative approach, data were collected through field observations, interviews with local historians, and documentation as well as other relevant written sources. Data analysis in this study followed three gradual activities: data reduction, data presentation, and conclusion drawing/verification. The findings reveal that in Menggala there are several buildings with historical value such as Masjid Kibang, Gedung Perwatin, the Post Office Building, the Tulang Bawang River dock, the House of Prince Warganegara, the tombs of Minak Ngengulung Sakti and Minak Sengaji, and Tangga Raja. These findings indicate that the buildings possess educational values relevant to the Social Studies curriculum under the Merdeka Curriculum. These historical sites can be linked to topics such as social interaction and social status, geographical conditions and natural resource conservation, and the development of Islam and culture in Indonesia. Therefore, utilizing these sites as learning resources can enrich students’ knowledge while fostering appreciation for local history. Integrating historical buildings into Social Studies learning can serve as an innovative and contextual strategy.